Selective Pre-concentration and Solid Phase Extraction of Mercury(II) from Natural Water by Alumina-Loaded 2-(2-Quinolylazo)-5-diethylamino Benzoic Acid Phases - Moghimi, Ali; Javad Poursharifi, Mohammad (Asian Journal of Chemistry, 2010)
Alumina phase loaded with 2-(2-quinolylazo)-5-diethylamino benzoic acid were synthesized based on chemical binding and physical adsorption approaches. The stability of a chemically modified 2-(2-quinolylazo)-5-diethylamino benzoic acid especially in concentrated hydrochloric acid which was then used as a recycling and pre-concentration reagent for further uses of alumina immobilized 2-(2-quinolylazo)-5-diethylamino benzoic acid. The application of this alumina for sorption of a series of metal ions was performed by using different controlling factors such as the pH of metal ion solution and the equilibration shaking time by the static technique. This difference was interpreted on the basis of selectivity incorporated in these sulfur containing alumina phases. Hg(II) was found to exhibit the highest affinity towards extraction by these alumina phases. The pronounced selectivity was also confirmed from the determined distribution coefficient (Kd) of all the metal ions, showing the highest value reported for Hg(II) to occur by alumina immobilized 2-(2-quinolylazo)- 5-diethylamino benzoic acid. The potential applications of alumina immobilized 2-(2-quinolylazo)-5-diethylamino benzoic acid for selective extraction of mercury(II) to occur from aqueous solution were successfully accomplished as well as pre-concentration of low concentration of Hg(II) (45 pg mL-1) from natural tap water with a pre-concentration factor of 200 for Hg(II) off-line analysis by cold vapour atomic absorption analysis.